Empowering mothers in increasing family resilience in the new normal era - Nurul Komariah; Kharisma Virgian; Desy Setiawati (Community Empowerment, 2021)
The new normal is a type of attitude and act of adjusting to the occurrence of certain conditions or events. Because the general public still lacks knowledge and has misconceptions about the new normal, they do not follow procedures such as wearing masks, washing hands, and physical distancing. The main objective of the service activity is to empower mothers to increase family resilience in the new normal period by increasing mothers' knowledge about Covid-19 prevention. The method of providing educational activities via WhatsApp groups. The activity took place in the Anyelir Posyandu's work area at the Dempo Health Center between August and September 2020. There was an increase in mother's knowledge at the end of the activity after being given education in the form of videos with the theme of new normal life and the discussion process.